Restricted diffusion in the corpus callosum: A neuroradiological marker in hypoxic–ischemic encephalopathy - Kale, Alok (Indian J Radiol Imaging, 2016)
BACKGROUND: Restricted diffusion within the splenium of the corpus callosum has been described by other authors in various conditions, however, restricted diffusion in the entire corpus callosum or isolated involvement of the splenium, genu, or body has been infrequently reported on magnetic resonance imaging (MRI) in neonatal hypoxic–ischemic encephalopathy. We report a series of cases showing different patterns of involvement. METHODS AND MATERIALS: Perinatal imaging with MRI including diffusion-weighted imaging was performed in 40 neonates with hypoxic–ischemic encephalopathy, including 11 premature neonates. Sixteen out of 40 patients demonstrated restricted diffusion within the corpus callosum. Out of 16 patients, 9 showed restricted diffusion in the entire corpus callosum, 4 had isolated splenium involvement, 2 had body and splenium signal abnormality, and 1 showed diffusion restriction only in the genu. CONCLUSIONS: Changes in the corpus callosum were also associated with more severe clinical presentation of encephalopathy. Restricted diffusion within the corpus callosum in infants with hypoxic–ischemic encephalopathy is often associated with extensive brain injury and appears to be an early neuroradiologic marker of adverse neurologic outcome.